Deep Learning Approaches for Voice Emotion Recognition Using Sentiment-Arousal Space - Tumanyan, Narek T. (Mathematical Problems of Computer Science, 2021)
In this paper, we present deep learning-based approaches for the task of emotion recognition in voice recordings. A key component of the methods is the representation of emotion categories in a sentiment-arousal space and the usage of this space representation in the supervision signal. Our methods use wavelet and cepstral features as efficient data representations of audio signals. Convolutional Neural Network (CNN) and Long Short Term Memory Network (LSTM) architectures were used in recognition tasks, depending on whether the audio representation was treated as a spatial signal or as a temporal signal. Various recognition approaches were used, and the results were analyzed.